Analisis Pembiayaan Sindikasi BPRS Muamalah Cilegon: Perspektif Fatwa DSN-MUI No. 91/DSN-MUI/IV/2014 - Nawawi, Ma'mun; Suganda, Asep Dadan; Hasanah, Irmatul (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2024)
The suitability of implementing syndicated financing in Sharia banks to the MUI DSN Fatwa is an important matter for several underlying reasons; first, Sharia banks have a fairly high risk if they provide financing with a nominal value exceeding the predetermined financing distribution limit. Second, the minimal level of supervision carried out by stakeholders in the implementation of syndicated financing carried out by Sharia banks and the low level of knowledge and insight of the community (customers), especially in Sharia-based syndicated financing. Third, it is not uncommon for misunderstandings or disputes to occur between customers and Sharia banks as a result of funding syndicated that does not meet Sharia compliance aspects. Fourth, the public does not fully believe that implementing syndicated financing by Sharia banks is by Islamic law. The results of the research show that there has been compatibility between the implementation of the funding syndicated of BPRS Muamalah Cilegon and the DSN MUI Fatwa Number 91/DSN-MUI/IV/2014. This can be seen from the suitability of the contract between fellow syndication participants, the terms of the agreement between the syndicated entity and the customer, and the provisions related to accounts and contract documents.